The use of simulation in occupational therapy education: A scoping review. (9th March 2021) - Grant, Terri; Thomas, Yvonne; Gossman, Peter; Berragan, Liz
Abstract: Introduction: Simulated learning experiences are a common feature of many health professions' pre‐registration curricula. However, the use of simulation within occupational therapy is still largely undefined. This scoping review seeks to identify and summarise the available evidence exploring the use of simulation within occupational therapy pre‐registration education. Methods: A search was conducted in four databases for articles published between 2009 and 2020 to identify international literature relevant to the use of simulation within occupational therapy education. Articles were evaluated using the appropriate Critical Appraisal Skills Programme (CASP) tool and key features and benefits of current simulation education were identified using thematic analysis. Results: A total of 32 papers were included within the review. Four themes were identified and explored: simulation methods, authenticity, global approaches to simulation, and relationship to practice education. Conclusion: Simulation is taking place in many different forms within occupational therapy internationally. It is positively received by students and may provide an effective replacement for practice education if focussed on professional standards and competencies. Further research into the potential effectiveness of simulation in relation to practice learning is indicated.